Metal‐Organic Framework Confined Solvent Ionic Liquid Enables Long Cycling Life Quasi‐Solid‐State Lithium Battery in Wide Temperature Range. Issue 37 (15th August 2022) - Liu, Zhaoen; Hu, Zewei; Jiang, Xueao; Wang, Xiwen; Li, Zhe; Chen, Zhengjian; Zhang, Yan; Zhang, Shiguo
Abstract: Solid‐state Li batteries are receiving increasing attention as a prospective energy storage system due to the high energy density and improved safety. However, the high interfacial resistance between solid‐state electrolyte and electrode results in sluggish Li + transport kinetics. To tackle the interfacial problem and prolong the cycle life of solid‐state Li batteries, a quasi‐solid‐state electrolyte (QSSE) based on a solvate ionic liquid (SIL) space‐restricted in nanocages of UIO‐66 (SIL/UIO‐66) is prepared in this study. Benefiting from the effective spatial confinement of the TFSI − by the pore UIO‐66 and the strong chemical interactions between the SIL and metal atoms, SIL/UIO‐66 QSSE exhibits high ionic conductivity and good compatibility with electrodes. As a result, Li|QSSE|LFP cells demonstrate excellent rate capability and cycle stability in a wide temperature range of 25–90 °C. This study provides a realistic strategy for the fabrication of safe solid electrolytes with excellent compatibility and long cycle life for high‐performance QSSE Li‐ion batteries. Abstract : A quasi‐solid‐state electrolyte based on a solvate ionic liquid space‐restricted in UIO‐66 exhibits excellent interfacial nano‐wettability, fast Li‐ion mobility, high ionic conductivity, and good compatibility with electrodes. As a result, the SIL/UIO‐66 material for quasi‐solid‐state batteries demonstrates excellent rate capability and cycle stability in a wide temperature range of 25–90 °C.